2015
DOI: 10.1039/c4ay02666g
|View full text |Cite
|
Sign up to set email alerts
|

In-gel detection of biotin–protein conjugates with a green fluorescent streptavidin probe

Abstract: Exploitation of the (strept)avidin-biotin interaction is extremely valuable in a variety of biotechnological applications. Biotin is often covalently linked to proteins or nucleic acids. Determination of the degree of biotinylation of such macromolecules is essential for downstream applications. There is currently a gap in simple yet efficient assays for rapidly quantitating protein biotinylation, as staple methods may produce unclear results or rely on immuno-or competitive assays. We present a simple and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…S4A) revealing a preferential destabilizing effect of 10a and 10b on Ec BirA. Using a GFP-based biotinylation activity assay, 11,21 we confirmed that 10b leads to Ec BirA-GFP inactivation (Fig. 5B).…”
supporting
confidence: 55%
“…S4A) revealing a preferential destabilizing effect of 10a and 10b on Ec BirA. Using a GFP-based biotinylation activity assay, 11,21 we confirmed that 10b leads to Ec BirA-GFP inactivation (Fig. 5B).…”
supporting
confidence: 55%
“…5A ). Peptide 5 was utilized in a traditional streptavidin-shift assay 35 , since its split-intein mediated capture and protein trans splicing was more effective than with peptides 6 and 7 (Fig. 5B ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of the well-documented strong and SDS-resistant binding between streptavidin and biotin, a streptavidin gel-shift assay (adapted from Fairhead and Howarth and Sorensen et al . 35 , 44 ) was used to confirm transfer of biotin moiety to hCNTF; the described PTS reaction setups yielding the putative non-biotinylated and biotinylated hCNTF products were mixed with streptavidin in PBS and the streptavidin-biotin binding allowed 3 hours in room temperature. Detection of hCNTF biotinylation and subsequent streptavidin binding was carried out by Western Blotting.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were purified as described for His-tagged proteins. Biotinylation yields were evaluated using either the Pierce Biotin quantitation Kit following the manufacturer's protocol (Thermo Fisher Scientific) or by an SDS-PAGE assay 66 .…”
Section: Methodsmentioning
confidence: 99%